(untitled) (Swiss Medical Weekly, 2025)
OBJECTIVE: To assess the association of patient and transport characteristics with mortality and morbidity of neonates who require interfacility transport in central Switzerland. METHODS: We conducted a retrospective single-centre cohort study including neonates transported by the neonatal transport service of the Bern University Children՚s Hospital between January 2019 and December 2022. We reviewed the transport protocols and electronic patient charts of the hospitalisation after transport, and investigated the association of patient characteristics, clinical management before transport and transport characteristics (transport mode, transport times, adverse events) with outcomes. The primary outcome was death or impairment; secondary outcomes were lengths of stay in the intensive care unit and hospital, inotrope-free days and respiratory support-free days following transport. RESULTS: Of 807 neonates who were included, 105 (13%) showed an unfavourable outcome (death: 25 patients, impairment at time of discharge: 80). We observed a significant association between patients’ diagnosis and primary outcome (p <0.001). Patients with a primary neurological disorder (n = 120, 14.9%) had a significantly higher risk of an unfavourable outcome (odds ratio [OR]: 5, 95% confidence interval [CI]: 2.46–10.9) compared to patients with a cardiac diagnosis. Death or impairment (primary outcome) was more likely to be observed in ground-transported patients than in air-transported patients (crude OR: 2.12, 95% CI: 1.20–4.07, p = 0.009). This effect remained significant after adjustment for the potential confounding effect of a selection of patient and administrative characteristics (adjusted OR: 2.23, 95% CI: 1.14–4.68, p = 0.018). Emergency transports, extended medical support before transport, a five-minute APGAR score <6 and a Sarnat score ≥2 were associated with an unfavourable outcome in the crude analysis, but not in the adjusted analysis. There was no significant association between stabilisation time or total transport time and primary outcome. CONCLUSIONS: Our study illustrates potential risk factors for morbidity and mortality in neonates requiring transport from the birth facility to a specialised neonatal care centre. The relevance of the primary diagnosis should influence logistical transport decision-making in the future. In particular, children with neurological diseases require special attention. As ground transport showed a worse outcome than air transport, the helicopter service might be considered more frequently. Transport times seem to be of less importance in regions with short transport distances, but optimising dispatch and call to arrival times would probably improve transport efficiency.